Predicting the Level of Academic Stress Using Ineffective Attitudes and Spontaneous Thoughts with the Mediation of Mindfulness in Students - Marzeh Haji Aghayi, Monireh; Mahmoudi, Armin; Hosseini Nik, Seyyed Soleyman (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: One type of stress related to learning environments is academic stress, which affects millions of students worldwide annually. This study was conducted to predict the level of academic stress using maladaptive attitudes and self-defeating thoughts with the mediating role of mindfulness in high school students in Torkaman city. Methods: The research method was correlation. The statistical population of the study was all high school students in Torkaman city in the academic year 2020-2021. A sample of 361 students was selected using multi-stage sampling. The research instruments included the Gadzela academic stress questionnaire (1991), the Hollon and Kendall self-defeating thoughts questionnaire (1980), the long version of the Weisman and Beck irrational beliefs scale (1978), and the five-factor mindfulness questionnaire by Baer and colleagues (2006). Results: The results of the structural equation modeling indicated a direct relationship between maladaptive attitudes and academic stress (β = 0.42, p < 0.001), an indirect relationship between maladaptive attitudes and academic stress through mindfulness (β = -0.17, P < 0.05), a direct relationship between negative self-defeating thoughts and academic stress (β = 0.4, p < 0.001), and an indirect relationship between negative self-defeating thoughts and academic stress through mindfulness (β = -0.14, P < 0.05). Therefore, the research model was confirmed based on significant indices and fit. Conclusion: This study, by investigating the dimensions of academic stress, negative self-defeating thoughts, and maladaptive attitudes in students, has taken a preliminary step towards creating a psychological therapy model in the future.